The Association Between Psychological Inflexibility and Mental Health during the Third Wave of COVID-19 Pandemic: english - Barzut, Vesna G.; Blanuša, Jelena D.; Knežević, Jasmina D.; Marinković, Gordana Ž. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This study aimed to compare the psychological functioning of people with different experiences with coronavirus infection in the second year of the pandemic (February–June 2021) and to explore the role of psychological inflexibility in the experienced level of distress. A total of 860 people (753 females, 429 COVID-19 convalescents) participated in this study. Results showed that people who experienced the hospitalization of a loved one reported higher levels of stress. On the other hand, people who had recovered from COVID-19 infections showed higher levels of anxiety but, interestingly, lower levels of stress compared to those who had not been infected with the coronavirus. Sequential mediation analysis revealed that psychological inflexibility had both direct and indirect effects on general distress, with the latter occurring via fatigue and subjective well-being. This study provided additional support for the importance of psychological flexibility in mental health, even during adverse times such as COVID-19 pandemic.
Keywords: COVID-19; mental health; subjective well-being; psychological inflexibility